The effect of cell concentrations from different cell populations on the viability of umbilical blood stem cells - Hauck-Dlimi, Barbara; Dlimi, Afif; Zimmermann, Robert; Eckstein, Reinhold; Zingsem, Jürgen (Clinical Laboratory, 2014)
In addition to bone marrow or peripheral blood derived stem cells, cord blood (CB) is an alternative source for hematopoietic stem cells. This report shows the impact of higher concentrations of leukocytes, mononu- clear cells (MNCs), and CD34-positive cells on the viability of CB derived stem cells after cryopreservation.Statistical analysis of data from 5520 CB units, prepared and cryopreserved from 2003 through 2011, was performed with appropriate software. Cell concentrations for leukocytes, platelets, red blood cells (RBCs), CD34-positive leukocytes, viable leukocytes, and MNCs were determined. The proliferation and differentiation capacity was assessed in cell culture assays.Content of leukocytes, CD34-positive leukocytes, and MNCs decreased after thawing. The recovery rate of colony forming units (CFUs) (29.05%) correlated significantly with leukocytes, platelets, RBCs, MNCs, CD34- positive leukocytes, and viable leukocytes. The recovery rate for erythroblasts (3.33%) correlated significantly with leukocytes, CD34-positive leukocytes, MNCs, and viable leukocytes. In the different cell concentration groups only RBCs showed a negative influence on viability. The concentrations of leukocytes, platelets, and CD34-positive leukocytes before cryopreservation correlated positively with the concentrations of leukocytes, CD34-positive leukocytes, MNCs as well as with the cell viability after thawing.Increased cell concentrations in CB do not limit the recovery of CD34-positive leukocytes nor the viability of leukocytes or the number of CFUs after thawing. On the contrary, CB units with high cell concentrations show a better outcome than units with low cell concentrations. Only RBCs seem to have a negative influence on CB quality.
EVALuna2:15987